Health Workers' Knowledge and Perceptions on Dementia in Skilled Nursing Homes: A Pilot Implementation of Teepa Snow's Positive Approach to Care Certification Course. Issue 3 (2018) - Ehlman, Mary C.; Nimkar, Swateja; Nolan, Beth A. D.; Thomas, Pamela; Caballero, Carlos E.; Snow, Teepa
Abstract : Introduction: A knowledge gap on caring for people with dementia exists among health workers employed in skilled nursing facilities. This article reports on knowledge gained and perceptions changed among 24 skilled nursing facility health workers who completed Teepa Snow's innovative Positive Approach to Care Certification course as a regional initiative. Methods: This pilot study used a quasi-experiment with a one-group pretest-posttest design to assess the dementia knowledge and perceptions of health workers who participated in the course. Paired responses ( n = 22) for the 54-item dementia knowledge and training/coaching perceptions survey were compared using the McNemar test, Paired t test, and Wilcoxon signed-rank test to analyze the improvement in knowledge and perceptions of dementia. Results: Significant knowledge gain was found among health workers after completing the program ( t (21) = −7.46, P < .001). Statistical differences ( P < .05) were present in eight knowledge items (ie, working memory, mental health, temporal lobe, "sapphire", "space and awareness", personal space, binocular vision, and hippocampus) and four perception areas (ie, approaching, understanding, calming, and instructing) about dementia. Significant changes were also found in four areas of health workers' perceptions about dementia ( P < .05). Discussion: The certification course can improve knowledge and facilitate perceptual change on dementia. Implementing this program as a novel regional initiative has robust potential in ensuring continuing workforce development in health care settings challenged with ever-changing people living with dementia needs and high staff turnover.